2006
DOI: 10.1136/vr.159.20.655
|View full text |Cite
|
Sign up to set email alerts
|

Use of metabolic profiles for the assessment of dietary adequacy in UK dairy herds

Abstract: Between April 1999 and March 2004, metabolic profile analyses were performed on individual blood samples from 35,506 dairy cattle in the UK. Assessment of the cows' energy status by the analysis of plasma samples for beta-hydroxybutyrate, glucose and non-esterified fatty acids showed that 70.4 per cent of the cows in early lactation (10 to 20 days calved), 57.1 per cent of the cows in mid-lactation (51 to 120 days calved) and 57.7 per cent of the dry cows within 10 days of their predicted calving date had one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 35 publications
3
40
1
8
Order By: Relevance
“…In recent years, the use of blood metabolites has acquired relevance for the study and diagnosis of nutritional imbalances due to its simplicity (Wittwer, 2000;Macrae et al, 2006). In this study, plasma concentrations of BHBA in all treatments were found above the range of normal values for dairy cows (averaging 1.01 mmol/L), which are considered acceptable from 0.1 to 0.6 mmol/L in early lactation (Wittwer, 2012;Raboisson et al, 2014).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In recent years, the use of blood metabolites has acquired relevance for the study and diagnosis of nutritional imbalances due to its simplicity (Wittwer, 2000;Macrae et al, 2006). In this study, plasma concentrations of BHBA in all treatments were found above the range of normal values for dairy cows (averaging 1.01 mmol/L), which are considered acceptable from 0.1 to 0.6 mmol/L in early lactation (Wittwer, 2012;Raboisson et al, 2014).…”
Section: Discussionmentioning
confidence: 59%
“…The measurement of specific metabolites allows the evaluation of adequacy of the main metabolic pathways associated with energy, protein, and minerals and then provides useful information related to nutrition and animal health to optimize the productive and reproductive potential of cows (Kida, 2003;Macrae et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…High MP cows also had higher concentrations of blood NEFA than LMP cows, which may be a result of a larger degree of fat mobilisation due to the greater energy deficit of the HMP cows. However, there was no significant difference in BCS change and the concentrations of blood plasma NEFA were within the overall normal range as outlined in Macrae et al (2006). There were no significant differences in the concentrations of urea and glucose in blood plasma between MP groups.…”
Section: Discussionmentioning
confidence: 68%
“…The HMP cows mobilised more body lipid reserves to sustain MP which has been reported to reduce BCS (Gallo et al, 1996) and increase blood ketone concentrations (Nikkhah et al, 2008). Studies have concluded that evidence for this trend may be shown by the concentrations of blood βHBA which is regarded as an indication of fat tissue mobilisation (Macrae et al, 2006;Nikkhah, et al, 2008); HMP cows had concentrations of blood βHBA that were significantly higher than other MP sub-groups. As the reduction in BCS was low, it is more likely that it was the increased DMI which led to the greater βHBA.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly a greater emphasis was placed on glucose and blood cell parameters and none measured the most common metabolites now used, BHB and non-esterified fat acids (NEFAs). Complete profiles are currently advocated to assess the adequacy of the transition period management (Macrae et al, 2006). Research has tended to focus on identification of metabolites as predictors of reduced fertility in individuals or herds and linked these measurements to evaluation of the causal mechanisms linking nutrition and fertility.…”
Section: Discrepancies In Terminology and Definitions Of Kpismentioning
confidence: 99%